Android Based E-Commerce Application Design For Fashion Store - Romadhon, Reza Rizki (STIE Miftahul Huda, 2025)
E-commerce is an online buying and selling platform that can make buying and selling transactions easily without the need for customers to come to the place to make purchases, just rely on cellphones, computers and the internet network to make transactions. Fashion Store is one of the many trading companies involved in the fashion world that only sells various products such as T-shirts, Jeans, Hats, Shoes etc. Fashion Shop products are products made locally, so far promotions from this shop have only been carried out via WhatsApp and Instagram media. In building an android-based sales system or commonly called e-commerce, the author uses code in the design. The method used is a prototype, where the data and information needed can be obtained through direct observation and interviews. By making this Android-based sales application, it can help sell products more efficiently, and can help manage sales data as well as product stock.